A cultural responsive landscape study on Perak Malay garden: an expressional value - Ismail, Nor Atiah; Nangkula, Utaberta; Mohd Yunus, Mohd. Yazid; Ismail, Sumarni (American-Eurasian Network for Scientific Information, 2015)
The residential landscape can be perceived as an expression of the intrinsic and cognitive values of a relationship between humans and their living environment. As an example, the Malay rural cultural garden reveals its significant intrinsic and cognitive values through its functional characteristics such as provision of food, medicine, cosmetics and shade. The importance of an intimate relationship between humans and gardens in residential areas has also been suggested by scholars who introduce the idea that landscape sometimes represents human personality and behaviour. The residential landscape means more than merely planting ornamental trees. Residential gardens promote certain feelings reflecting human adaptation to the spaces, creating a responsive living environment. This responsive environment is a space for inhabitants to express their physical activities, emotions, social and cultural demands.